Make like a man: the demands of creative work, gender and the management of everyday life. (1st January 2007) - Bettina-Johanna Krings
Abstract : Drawing on a study in the multimedia sector in Stuttgart, Germany, this paper argues that the living and working conditions of women have adapted strongly to the traditional breadwinner concept and that this change has major consequences for general social and cultural development. The study concludes that a historical shift from 'maternal spaces' to the breadwinner model is a sign of deep changes in the reproductive sphere. It analyses the temporal organisation of work-life balance and finds that, although women have gained access to some highly-skilled positions in the labour market which have granted them new forms of autonomy and independence, they have also been exposed to new forms of stress. These pressures are experienced in a range of different ways both by childless women and those with children, leading to a variety of strategies for managing daily life, each of which entails some losses, as well as gains. Although a critique of the modernisation of working cultures has been opened up, this paper argues that in order to explain the societal impacts of these changes there is a need for further exploration of both the perception and the quality of the losses experienced by women in these change processes.